2008
DOI: 10.1309/y16qcxe3ygmxx19q
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fine Needle Aspiration Cytology for the Distinction of Pancreatic Mucinous Neoplasia

Abstract: Cytology frequently has some role in preoperatively distinguishing pancreatic mucus-producing neoplasia (intraductal papillary mucinous neoplasms [IPMNs] and mucinous cystic neoplasms [MCNs]) from other pancreatic cysts. We evaluated all cytologic specimens at our institutions from resected pancreatic cystic lesions for lesional extracellular and cellular material. Lesional extracellular material was identified in 32 of 38 of the cytologic samples from cystic pancreatic mucus-producing neoplasms (28 of 31 IPMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In our study, 77% of the specimens had epithelium adequate for interpretation, which was higher than has previously been reported for standard FNA. 23 There have been only a few other reports of alternate methods for sampling the cyst wall itself during EUS-FNA to achieve higher diagnostic yields. One study, for example, used a larger caliber biopsy needle ("trucut") to obtain a core biopsy of the cyst wall in 10 patients and showed a diagnostic accuracy of 70% compared with 0% for cyst fluid cytology.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 77% of the specimens had epithelium adequate for interpretation, which was higher than has previously been reported for standard FNA. 23 There have been only a few other reports of alternate methods for sampling the cyst wall itself during EUS-FNA to achieve higher diagnostic yields. One study, for example, used a larger caliber biopsy needle ("trucut") to obtain a core biopsy of the cyst wall in 10 patients and showed a diagnostic accuracy of 70% compared with 0% for cyst fluid cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic cytological features of IPMNs are extracellular mucin and papillary clusters of mucinous epithelium with a variable degree of atypia [48,49,50]. Features suggesting high-grade IPMN include papillary clusters and loss of honeycomb structures with coarse chromatin, irregular nuclear membrane, and high nuclear-to-cytoplasmic ratio [49].…”
Section: Ipmnmentioning
confidence: 99%
“…The hallmark feature in cytology for a neoplastic mucinproducing cyst (either MCN or IPMN) includes the presence of thick extracellular mucin (neoplastic mucin; Figure 1, a). 11, 12 Stelow et al 13 reviewed the fine-needle aspirations of 31 IPMNs and found extracellular mucin in a majority of these lesions. Other cytologic features for IPMN (and MCN) include mucinous glandular epithelial cells in groups, papillary clusters, single cells with varying degrees of cytologic atypia, and cyst debris (Figure 1, b).…”
Section: Intraductal Papillary Mucinous Neoplasmmentioning
confidence: 99%